THE EFFECT OF LEADERSHIP AND ORGANIZATIONAL COMMUNICATION TOWARD EMPLOYEE WORK MOTIVATION AT DINAS PENDIDIKAN PESISIR SELATAN REGION - Sentot Mintarjo; Bustari Muchtar (Program Studi Magister Manajemen, 2014)
The aim of this study is to analyze : 1) The effect of leadership on the organizational communication and work motivation of employee in Dinas Pendidikan in Pesisir Selatan Region, 2) The influence of organization communication on the work motivation of employee in Dinas Pendidikan in Pesisir Selatan. The population of this study all the employee who worked in the Dinas Pendidikan in Pesisir Selatan is 83 person. Invite sample size is 68 respondens which selected based on the stratified Proportional random sampling. To answer the research question, the path analisys is used. The study showed that leadership had positive & significant effect on the organizational communication & work motivation in Dinas Pendidikan in Pesisir Selatan. The organizational communication significantly afected the work motivation of employee in the Dinas Pendidikan in Pesisir Selatan Region